Analisis Keputusan Investasi: Tinjauan Literatur Sistematis - Ni Putu Shinta Dewi; Isti Fadah (Widya Manajemen, 2025)
This systematic literature review examines the key theories and factors influencing investment decision-making, based on 25 articles published between 2019 and 2024. The study highlights the role of behavioral finance and prospect theory in explaining how psychological biases, such as overconfidence and loss aversion, impact investor behavior. Financial literacy is identified as a critical factor in promoting informed decision making, while socio-economic and cultural factors, such as age and education, also shape investment preferences. The growing significance of sustainable finance, driven by environmental, social, and governance (ESG) considerations, is also discussed. The review emphasizes the need for future research to explore the interaction of these factors for better investment outcomes.